‘Competent’ or ‘Considerate’? The Persistence of Gender Bias in Evaluation of Leaders - Denise, Salin (Nordic Journal of Working Life Studies, 2020)
The aim of this article is to analyze the possible persistence of gender bias in the evaluation of leaders in Finland. Findings are based on two different studies. The first study confirmed that the perceived effectiveness and likeability ratings of fictive leaders (n = 358) varied as a function of leader gender. The second study, based on qualitative content analysis of subordinates’ descriptions (n = 119) of good and poor leaders, pointed to gendered differences in the dimensions that subordinates paid attention: female leaders were both more likely than men to be praised for having, and criticized for not having, communal traits, whereas men were more likely than women to be judged on their expertise. As Finland has consistently been rated one of the most gender-equal countries in the world, these findings can be seen as particularly strong evidence of the persistence of gender bias in evaluations and of ongoing gendering of leadership.